(untitled) (Journal on Excellence in College Teaching, 2024)
The authors asked students enrolled in a wide range of college mathematics courses to predict their scores on quizzes and exams. They found that top and bottom performers were less accurate predictors, but those scoring in the middle range were more accurate in predicting their scores. Females were more accurate predictors of their scores than males. Results showed that self-assessment behavior is a function of performance on individual academic assignments. Students self-assessed their performances differently according to how they performed on assignments. The self-assessment accuracy of low-performing students improved over time when they were continuously asked to predict their scores. Results showed that improved self-assessment accuracy was also linked to higher academic achievement for those students.